Interactive Information Visualization as Support for Computer-Aided Diagnosis: Prototype and Qualitative Evaluation - Alvim, Larissa Terto; Gonçalves, Vagner Mendonça; Ribeiro, Matheus A. O.; Nunes, Fátima L. S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de Informação, 2026)
Research Context: Medical Information Systems (MIS) have evolved significantly to achieve efficiency and scalability in processing large amounts of multimodal data. Computer-Aided Diagnosis (CAD) models offer a second opinion to help physicians compose a more precise diagnosis. Effective CAD models need to be built on diverse, multicentric and, in specific cases, multimodal databases. Scientific and/or Practical Problem: The lack of standardization and complex interoperability among different MIS are major challenges that hinder the exploration of the maximum potential of digital data in healthcare applications, including the development of CAD models. Proposed Solution and/or Analysis: A generic, flexible and reusable relational data model was applied, developed specifically to support the training of CAD models from multimodal data. Through a case study using Cardiac Magnetic Resonance exams, a prototype with interactive Information Visualization (IV) functionalities was developed and qualitatively evaluated. Related IS Theory: The evaluation was inspired by the Fit-Viability Theory, as the prototype was evaluated primarily with regard to its potential for effective integration into real-world clinical workflows. Research Method: The research included: literature review; modeling; prototyping; development; qualitative evaluation through interviews with health professionals; and analysis and summarization of results. Summary of Results: Evaluated IV tools demonstrated strong potential to enhance clinical decision-making for the interviewed health professionals. From a Fit-Viability perspective, the system showed a promising fit with the users’ analytical needs and clinical workflows, while also indicating viability in terms of technical feasibility and resource compatibility within the healthcare setting. Contributions and Impact to IS area: Results showed that the strategic combination of a flexible data model and customizable IV functionalities can provide valuable research tools and diagnostic aids to physicians. These insights offer practical guidance for enhancing MIS and CAD capabilities, particularly in supporting the effective analysis of medical databases.